2001
DOI: 10.1097/00043426-200102000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Dysfunction as the Presenting Feature of Acute Lymphoblastic Leukemia

Abstract: Current protocol guidelines for dose modification for liver disease may be overly stringent and modification may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Yet, the preponderance of dose‐adjustment recommendations remain derived from these early studies with limited data to update guidelines for monitoring and dose modifications of many mBFM agents . Management of TRT during induction also remains controversial, with data supporting either dose‐modification or full‐dose chemotherapy to achieve remission . The rare recurrence of hepatotoxicity following resolution supports continuing without modification of subsequent hepatotoxic chemotherapy, but we found that approximately 15% of our cohort received a dose reduction due to laboratory evidence of severe hepatotoxicity, including one time elevation of isolated AST or ALT, or for pancreatitis.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Yet, the preponderance of dose‐adjustment recommendations remain derived from these early studies with limited data to update guidelines for monitoring and dose modifications of many mBFM agents . Management of TRT during induction also remains controversial, with data supporting either dose‐modification or full‐dose chemotherapy to achieve remission . The rare recurrence of hepatotoxicity following resolution supports continuing without modification of subsequent hepatotoxic chemotherapy, but we found that approximately 15% of our cohort received a dose reduction due to laboratory evidence of severe hepatotoxicity, including one time elevation of isolated AST or ALT, or for pancreatitis.…”
Section: Discussionmentioning
confidence: 86%
“…2,30,42 Management of TRT during induction also remains controversial, with data supporting either dose-modification or full-dose chemotherapy to achieve remission. [43][44][45][46] The rare recurrence of hepatotoxicity following resolution supports continuing without modification of subsequent hepatotoxic chemotherapy, but we found that approximately 15% of our cohort received a dose reduction due to laboratory evidence of severe hepatotoxicity, including one time elevation of isolated AST or ALT, or for pancreatitis. These dose modifications are consistent with current protocol recommendations, but do not account for growing controversy over whether serum markers represent true hepatic dysfunction.…”
Section: Ta B L E 4 Predictors Of Cumulative Incidence Of Pancreatitismentioning
confidence: 77%
“…When blast cells are not visible on the smears, other diagnoses may be considered such as viral or autoimmune hepatitis combined with pancytopenia, hepatitis-associated aplastic anemia syndrome, or poisoning. In some of the cases reported so far, there were precautions taken in the use of chemotherapy in children with high levels of serum aminotransferase activities and/or conjugated serum bilirubin concentrations, using steroids and delaying chemotherapy until the liver tests improved and/or reducing the dose of chemotherapy (1,7,8). Acute lymphoblastic leukemia of the pre-B type is the most commonly observed, but other types are possible, as shown by patient 6.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid and, if necessary, repeat bone marrow examination is therefore essential. These precautions were taken for fear of an increased toxicity of vincristine, asparaginase, and daunorubicin because of their hepatic metabolism (1,7,9). The improvement in liver biochemical results in the course of chemotherapy indicates that the liver condition is the consequence of the leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…A balance has to be struck between effective treatment of the leukaemia and preservation of liver function. Kelleher et al [3] recommended and justified the use of these agents at relatively higher dose than recommended in hepatic dysfunction to achieve early remission, with the possible advantage of clearing the tumour from the liver quickly and improving the hepatic function. Nevertheless, supportive treatment and specific prophylaxis against tumour lysis syndrome is essential in the presence of FHF.…”
mentioning
confidence: 99%